The Internet as a source of information on health and disease - Martyna Warchoł; Marzena Furtak - Niczyporuk; Patrycja Gierszon; Magdalena Stypuła (Kazimierz Wielki University, 2018)
The Internet has become a significant factor influencing the public health area. It contributes to higher awareness of the health problems in the society and to the greater self-reliance of the patients, it helps to carry out the health promotion campaigns and health education with more effectiveness. Having at our disposal an enormous reserves of specialized knowledge, we become more and more aware patients. One of the most frequent usages of the Internet in the context of one's health is searching for the medical information - whether it is for the diagnosis, finding the proper form of treatment, looking into the opinion of given specialist, make an appointment with a doctor, collect the results of examinations and so on. The Internet has become one of the most important sources of medical information, and the information on health. However, it also poses a certain threats to the health. It may be used to propagate disadvantageous or even dangerous behaviours, to distribute the addictive or other harmful substances, to promote substances of alleged healthy effectiveness, and to spread untested methods of treatment that is contradictory with modern medical knowledge.